1999
DOI: 10.1111/j.1745-6584.1999.tb01113.x
|View full text |Cite
|
Sign up to set email alerts
|

The Channel Network Model—A Tool for Transport Simulations in Fractured Media

Abstract: The Channel Network model and its computer implementation, the code CHAN3D, are presented for simulations of fluid flow and transport of solutes. The tool may be used to simulate and interpret field experiments of flow and transport on a large or small scale. It also may also be used for performance and safety assessments of repositories for nuclear and other hazardous wastes, e.g., chemical wastes. From observations in the field it is deduced that the flow and transport take place in a three‐dimensional netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 10 publications
0
28
0
1
Order By: Relevance
“…15 Dependence of the breakthrough curves of the multichannel model on channel geometry together with its implementation into, e.g. the channel network model (Gylling et al 1999), will be made in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Dependence of the breakthrough curves of the multichannel model on channel geometry together with its implementation into, e.g. the channel network model (Gylling et al 1999), will be made in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, still a long way to go before implementing it into, e.g. the channel network model (Gylling et al 1999) for safety and performance assessment of deep geological repositories for spent nuclear fuel. In particular, the capability and malleability of the multi-channel model in interpreting fieldscale experiments should be extensively studied in the near future.…”
Section: Dependency On Channel Width and The Mean Flow Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Following Neretnieks (1983), it has become increasingly apparent that even within a fracture, water flow tends to concentrate through channels, which occupy a relatively small portion of the aquifer (Neretnieks, 1993;Tsang and Neretnieks, 1998). This led to the definition of channel network models, which can be viewed as a particular example of fracture network models, where preferential flow paths within fracture planes are represented through channels (Neretnieks, 1983;Moreno and Neretnieks, 1993;Gylling et al, 1999). Moreno and Tsang (1994) showed that channeling can be caused by multigaussian (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the complexities of the system, it is shown that the analytical solution to the Laplace‐transformed concentration at the outlet of the flowing channel is a product of two exponential functions; they describe the contributions of two partial systems in parallel in retarding solute transport, respectively. As a result, the Laplace‐transformed solution can readily be included in both the discrete fracture network models [ Dershowitz et al ., ] and the channel network models [ Gylling et al ., ] to describe solute transport through channels in heterogeneous fractured media consisting of an arbitrary number of rock units with piecewise constant properties. More importantly, the Laplace‐transformed solution suggests that the large number of different individual parameters can be grouped into a small set of parameter groups that considerably reduce the number of independent parameters.…”
Section: Introductionmentioning
confidence: 99%